Effectiveness of Using Local Wisdom-Based Teaching Materials on Understanding Family Genealogy Material in Class II Students of UPT SD Negeri 002 Kuapan - Hammy, Setia Febriani; Guslinda, Guslinda; Munjiatun, Munjiatun (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to see the effectiveness of using local wisdom-based teaching materials on understanding family tree material in class II students at UPT SD Negeri 002 Kuapan. The type of approach used in this research is a quantitative approach with experimental methods. The form of this research is Pre-Experimental with a One-Group-Pretest-Posttest Design research design. The subjects of this research were class II students at UPT SD Negeri 002 Kuapan as an experimental class. This research used teaching materials based on local wisdom in two learning meetings. The research results show that the pretest results obtained an average of 57.40 and the posttest results were 86.80. Hypothesis test calculations obtained a sig (2-tailed) result of 0.000 0.05 which shows that there is a significant difference in increasing understanding of family genealogy material in class II students at UPT SD Negeri 002 Kuapan before and after using local wisdom-based teaching materials. Based on the results of the N-Gain test, it was found that the experimental class learning outcomes increased by 71.56% in the high and effective category. In observing students' learning activities at meetings I and II, the average percentage score was 81.4% and 82.8% in the Active category.